Continuous cultures of Clostridium acetobutylicum: culture stability and low-grade glycerol utilisation - Andrade, José Carlos (2011)
Continuous cultures of two strains of Clostridium acetobutylicum were stable for over 70 d when grown on glucose/ glycerol mixtures. Butanol was the major fermentation end-product, accounting for 43 to 62% (w/w) of total products. Low-grade glycerol [65% (w/v) purity] could replace commercial glycerol [87% (w/v) purity], leading to a similar fermentation pattern: a butanol yield of 0.34 (mol/mol), a butanol productivity of 0.42 g l−1 h−1 and a 84% (w/w) glycerol consumptionwere attained when cultures were grown at pH 6 and D = 0.05 h−1; butanol accounted for 94% (w/w) of total solvents. These values are among the highest reported in literature for C. acetobutylicum simple chemostats.